Leveraging Immunopeptidomics To Study and Combat Infectious Disease - Owen K. Leddy; Forest M. White; Bryan D. Bryson (mSystems, 2021)
T cells must recognize pathogen-derived peptides bound to major histocompatibility complexes (MHCs) in order to initiate a cell-mediated immune response against an infection, or to support the development of high-affinity antibody responses. Identifying antigens presented on MHCs by infected cells and professional antigen-presenting cells (APCs) during infection may therefore provide a route toward developing new vaccines.